2018
DOI: 10.1002/prop.201800069
|View full text |Cite
|
Sign up to set email alerts
|

Double Field Theory for the A/B‐Models and Topological S‐Duality in Generalized Geometry

Abstract: We study AKSZ‐type BV constructions for the topological A‐ and B‐models within a double field theory formulation that incorporates backgrounds with geometric and non‐geometric fluxes. We relate them to a Courant sigma‐model, on an open membrane, corresponding to a generalized complex structure, which reduces to the A‐ or B‐models on the boundary. We introduce S‐duality at the level of the membrane sigma‐model based on the generalized complex structure, which exchanges the related AKSZ field theories, and inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Applying the strategy developed in [36] for the construction of T-duality invariant membrane sigma-models could be helpful in that case, although its precise implementation is not straightforward. In addition, one should then deal with the section condition and understand its geometric origin in the context of weaker algebroid structures, similar to the (pre-)DFT algebroids defined in [36] and formulated in [69] in terms of an AKSZ-type construction.…”
Section: Discussionmentioning
confidence: 99%
“…Applying the strategy developed in [36] for the construction of T-duality invariant membrane sigma-models could be helpful in that case, although its precise implementation is not straightforward. In addition, one should then deal with the section condition and understand its geometric origin in the context of weaker algebroid structures, similar to the (pre-)DFT algebroids defined in [36] and formulated in [69] in terms of an AKSZ-type construction.…”
Section: Discussionmentioning
confidence: 99%
“…The precise relation between the two models is clarified in[82], where it is shown that the degenerate limit Π = 0 of the Courant sigma-model of[51] with a particular BV gauge-fixing coincides exactly with the R-twisted membrane sigma-model of[9].…”
mentioning
confidence: 99%
“…As we have verified based on its properties, the DFT structure indeed reduces to the canonical Courant algebroid under the strong constraint. The DFT algebroid is later formulated in the graded symplectic geometry in [30]. When one of the five properties of Courant algebroid, namely the Jacobi identity is violated, one gets a structure called pre-Courant algebroid, described originally in [8].…”
Section: Pos(corfu2018)132mentioning
confidence: 99%